Student Worksheets Based on HOTS-Oriented Case Studies to Improve Critical Thinking Skills of Fourth-Grade Elementary School Students - I Made Rai Aditya Wiranata; I Made Ardana; Ni Ketut Suarni (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Low critical thinking skills are the main problem of this research. This research aims to develop LKPD based on HOTS-oriented case studies on material changing the shape of objects in class IV elementary school. This research is of the research and development (R&D) type using the ADDIE development model. The main data comes from the subjects of class IV students at SD No. 2 Gulingan, Mengwi District, totaling 25 students. Data was analyzed descriptively and quantitatively. Data were analyzed through validity and practicality tests with average ranges and effectiveness analysis with t-tests. Experts assess the validity test, the practicality test is assessed by teachers and students as practitioners, and the effectiveness test is a field test on students to see its effectiveness on critical thinking abilities. Based on the average assessment results of content and media experts, the results were 93.33% and 94.80% with very good qualifications. Then, the average result of the practicality test by teachers was 92.73% with very good qualifications, and from students, it was 94.28% with very good qualifications. Based on trials on students, the obtained significance value (2-tailed) < 0.05, namely 0.00 < 0.05, so the LKPD developed was declared effective in improving the critical thinking skills of fourth-grade students in elementary school. So, the HOTS-oriented case study-based LKPD material on changes in the form of objects in class IV elementary school, which was developed, is suitable as teaching material because it has been proven to be valid, practical, and effectively used to improve the critical thinking skills of class IV elementary school students.